The general principles of vibration treatment process description with the external source of dynamic influence - Калмыков, Михаил Александрович; Струтинский, Василий Борисович; Щелоков, Вадим Сергеевич (Eastern-European Journal of Enterprise Technologies, 2012)
In-process within the framework of phenomenological approach the basic requirements are formulated to the mathematical model of motion of working environment of vibrosetting in flat case, when the external variable power field of excitation has a turbulent constituent